Community Empowerment through Humic Acid Training in Sukodono Sidoarjo District - Nabila, Annisa Lu'lu'un; Pangesti, Yohana Fransisca Eka; Lestari, Dewi Anggun; Faiziah, Adinda; Setiawan, Risqi Firdaus (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Sukodono District, Sidoarjo, experienced soil degradation due to the excessive use of chemical fertilizers without the accompaniment of organic fertilizers. As a solution, training on making humic acid from water hyacinth was carried out in Plumbungan Village on May 14–23, 2025. This activity aims to improve farmers' knowledge and skills in processing local organic matter into environmentally friendly liquid fertilizer. The training included socialization, leaflet distribution, and direct practice of fermenting water hyacinth with additional rice washing water, brown sugar, and MOL. The results of the activity show an increase in farmers' understanding and enthusiasm for the use of plant waste as organic fertilizer. Humic acid is considered to be able to improve soil structure and increase agricultural yields. This program is the first step to encourage sustainable agriculture and make farmers more independent in using local resources productively. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 12: Responsible Consumption & ProductionSDG 13: Climate ActionSDG 15: Life on Land